Parallel Hurrian and Hittite šumma izbu Omens from Hattuša and Corresponding Akkadian Omens - Cohen, Yoram (2017)
This article discusses the remains of the šumma izbu omen series from Hattuša. It will identify two previously misidentified Hurrian fragments as belonging to the omen series and demonstrate that they are parallel to Hittite šumma izbu omens found at Hattuša and Akkadian šumma izbu omens from elsewhere.
Keywords: Hittite and Hurrian divination; transmission and reception of cuneiform literature; the šumma izbu omen series; Ancient Near Eastern divination